2011
DOI: 10.1021/je2001683
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Growth of Gemini Surfactant (12-s-12) Micelles as a Modulate by Spacers: A Thermodynamic and Small-Angle Neutron Scattering (SANS) Study

Abstract: A series of symmetrical cationic gemini surfactants of the type N,N 0 -didodecyl-N,N,N 0 ,N 0 -tetramethylalkane-R, ω-diammonium dibromide "12-s-12" (s = 2, 4, 6, 8, 10, and 12) are synthesized, and their micellization study in aqueous solution is systematically reported. Specific conductivity as a function of surfactant concentration was measured, and critical micelle concentration (CMC), degree of counterion dissociation (R) of the micelle, and thermodynamic parameters, namely, Gibbs energy (ΔG m ), enthalpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…However, change in behaviour occurs much earlier in the case of a salt addition than in aqueous solution. a flexible loop or wicket-like arrangement is seen where the long spacer remains outward from the interface, occupying a larger area per molecule (A min ) [28][29][30][31]. This Br À has a greater ability to penetrate the Stern layer or interact with the quarternised triphenylphosphonium cation, thereby undergoing condensation and neutralising the overall charge on the micellar surface.…”
Section: Effect Of Saltmentioning
confidence: 99%
“…However, change in behaviour occurs much earlier in the case of a salt addition than in aqueous solution. a flexible loop or wicket-like arrangement is seen where the long spacer remains outward from the interface, occupying a larger area per molecule (A min ) [28][29][30][31]. This Br À has a greater ability to penetrate the Stern layer or interact with the quarternised triphenylphosphonium cation, thereby undergoing condensation and neutralising the overall charge on the micellar surface.…”
Section: Effect Of Saltmentioning
confidence: 99%
“…Additionally, an increase in the temperature causes a decrease in the charge density at micellar surface by lowering the aggregation number of micelle which leads to increase in a. [44,45] Information of temperature dependence of CMC and a value facilitate the calculation of the enthalpy of micellization [5,13,29,30,34] DH m ¼ À2RT 2 ð2 À aÞ d ln X CMC dT : ½3…”
Section: Thermodynamic Parameters Of Micellization In Presence Of Fixmentioning
confidence: 99%
“…One of the fundamental and important factors that contributes negatively (i.e., makes DH m more negative) is the release of more arranged water molecules (than bulk water) surrounded to hydrophobic surfactant tail; during transformation of tail from bulk phase to micellar phase. [44,47] Other important interaction that contributes negatively to DH m is repulsive electrostatic interaction between head groups. From the above facts, and as discussed earlier; the presence of glycols due to their hydrogen bonding ability increases repulsion between the ionic heads.…”
Section: Thermodynamic Parameters Of Micellization In Presence Of Fixmentioning
confidence: 99%
“…A series of symmetrical cationic gemini surfactants are synthesized, and their micellization study in aqueous solution is systematically reported. [36] Small-angle neutron scattering (SANS) inferred the presence of few morphological geometries ranging from spherical to rodlike micelles. [36] The mixed micellization, surface properties, and solubilization of mixtures of cationic gemini with conventional surfactants were studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Small-angle neutron scattering (SANS) inferred the presence of few morphological geometries ranging from spherical to rodlike micelles. [36] The mixed micellization, surface properties, and solubilization of mixtures of cationic gemini with conventional surfactants were studied in detail. [37] The cmc value of DTAB was reduced to one-sixth of its original value in the presence of a small amount of gemini surfactant.…”
Section: Introductionmentioning
confidence: 99%